MODEL PENDIDIKAN KARAKTER INTERAKTIF (TRANSFORMASI DISIPLIN SISWA MELALUI KREATIVITAS PEMBELAJARAN) - Ika Nur Safitri; Adiyono Adiyono (CV. ADIBA AISHA AMIRA, 2023)
This research aims to explore the impact of implementing the Interactive Character Education Model in an educational context. The main focus of the research is to understand how an interactive character education model can influence the transformation of student discipline through creativity in learning. The approach used in this research is qualitative, in collecting data the author uses research methods with Observation, Interviews and Documentation. This research was carried out at MAN Paser from May 2 2023. The results of this research are that the discipline and responsibility at MAN Paser is good, this is proven from the results of data presentation and interviews. The character of discipline and responsibility is always applied by teachers both in the classroom and outside the classroom. As for always arriving on time, neatly dressed. If there are students who violate discipline, the madrasah will provide sanctions aimed at providing a deterrent effect to students. Supporting factors: a) direct and active control from the Head of the Madrasah; b) there is an active role from teachers, c) there is an active role from parents of students, d) awareness of students, Inhibiting factors: family factors, environmental factors and friends. The application of interactive character education models in learning can produce significant improvements in student discipline. Creativity in learning is a powerful tool in stimulating student interest and involvement in the educational process. Through this interactive approach, students have the opportunity to understand positive character values, such as integrity, cooperation, responsibility, and others, in a context that is relevant to their daily lives.